Are covered faces eye-catching for us? The impact of masks on attentional processing of self and other faces during the COVID-19 pandemic. (April 2022) - Żochowska, Anna; Jakuszyk, Paweł; Nowicka, Maria M.; Nowicka, Anna
Abstract: During the COVID-19 pandemic, we have been confronted with faces covered by surgical-like masks. This raises a question about how our brains process this kind of visual information. Thus, the aims of the current study were twofold: (1) to investigate the role of attention in the processing of different types of faces with masks, and (2) to test whether such partial information about faces is treated similarly to fully visible faces. Participants were tasked with the simple detection of self-, close-other's, and unknown faces with and without a mask; this task relies on attentional processes. Event-related potential (ERP) findings revealed a similar impact of surgical-like masks for all faces: the amplitudes of early (P100) and late (P300, LPP) attention-related components were higher for faces with masks than for fully visible faces. Amplitudes of N170 were similar for covered and fully visible faces, and sources of brain activity were located in the fusiform gyri in both cases. Linear Discriminant Analysis (LDA) revealed that irrespective of whether the algorithm was trained to discriminate three types of faces either with or without masks, it was able to effectively discriminate faces that were not presented in the training phase.